Future perspectives in modulator therapies for Cystic Fibrosis: Advances and challenges (Research, Society and Development, 2024)
Cystic fibrosis (CF) is a complex and progressive autosomal recessive genetic disease caused by mutations in the CFTR gene, affecting multiple systems of the human body, mainly the pulmonary and digestive systems. This article aims to review current therapies and challenges faced in CF treatment, focusing on CFTR modulator therapies. A review of the available scientific literature on the subject was conducted, including articles from specialized journals, clinical studies, and systematic reviews from the past 10 years. Studies addressing current therapies, mechanisms of action of CFTR modulator therapies, treatment challenges, and future perspectives were selected. The data were analyzed and synthesized to provide a comprehensive view of the current state and future directions in the field of cystic fibrosis treatment.